Catch me (if you can): Assessing the risk of SARS-CoV-2 transmission via euro cash - Barbora Tamele; Alejandro Zamora-Pérez; Chiara Litardi; John Howes; Eike Steinmann; Daniel Matthias Todt (European Central Bank (ECB), 2021)
In the light of fears that the SARS-CoV-2 virus might be transmitted via cash - fears that were stoked by statements in the media and from public authorities - this paper aims to address the following issues: (1) to provide a descriptive account of the change in the circulation of euro banknotes and the use of cash in transactions during the pandemic; and (2) to assess the survivability of the virus on cash and the potential transmission risks. The pandemic has caused a significant increase in demand for cash as a store of value but a decrease in the use of cash in transactions. Although citizens reported using cash less in transactions partly out of fear of infection, research confirms that the risk of the virus being transmitted by banknotes and coins is very low. This supports the findings from the scientific community concluding that SARS-CoV-2 mainly spreads via respiratory fluids and airborne transmission, and that surfaces play a very minor role.
Keywords: I10; I12; E41; E58; 330; COVID-19 pandemic; SARS-CoV-2 virus; survivability; transferability; safety; banknotes; coins; cash demand; cash use